It all began with George Sand. Novelistic portraits of Fryderyk Chopin and his music in foreign literature. A survey - Maciąg, Kazimierz (Interdisciplinary Studies in Musicology, 2018)
The literary works discussed in this article exploit the motif of Fryderyk Chopin and his oeuvre in a variety of ways. The earliest novel is Lucrezia Floriani (1846), penned by the French writer George Sand, Chopin’s companion. The creation of Prince Karol (Chopin’s name in the novel), as if “detached” from the Polish composer’s biography, is an interesting, although none too original (even within the context of Sand’s oeuvre) example of the Romantic hero. Popular output, aimed at a readership seeking above all scandal and emotion, is represented by the German writer Hermann Richter’s novel Drei Frauen um Chopin (1935) and the contemporary thriller of collective authorship The Chopin Manuscript (2008). In these works, the composer is a tool designed to give readers the illusion of becoming acquainted with his biography or to interest sensation-seekers. Artistically the most interesting novel is Preludes, by the Danish writer Peer Hultberg (1989). Besides its original artistic form, the author is the only one to deal with musical material, attempting to present in prose that which ought to form the heart of every work about the brilliant musician, but which was achieved only by Cyprian Norwid in Fortepian Szopena [Chopin’s piano].